Thyroid hormones and prognosis in adults with status epilepticus: a retrospective study - Fu, Jie; Chen, Xiu; Li, Jinglun; Peng, Lilei (Frontiers in Endocrinology, 2024)
Objectives: Thyroid hormone levels have been indicated to be associated with the functional outcome in critical illness. However, the studies on thyroid hormones and status epilepticus (SE) are rare. This study aimed to evaluate the predictive value of serum thyroid hormone levels on admission for unfavorable outcome in adult patients with SE. Methods: We investigated and validated the predictive value of serum thyroid hormone levels on admission for the prognosis of adult SE patients. We extracted the clinical information and outcomes of patients. Modified Rankin scale (mRS) scores were applied to assess the patients' functional outcome, and mortality at 30 days after SE onset was identified. Serum levels of thyroid hormones including free thyroxin (FT4), free triiodothyronine (FT3) and thyroid-stimulating hormone (TSH) were detected on admission. Results: We first analyzed the discovery cohort of 87 patients with SE. We found that 35.6% (31/87) of the patients had a poor outcome at discharge, and 18.4% (16/87) of the patients died during hospital stay and at 30-day follow up. The serum FT3 levels in the non-survivors group were significantly lower than those in the survivors group.Low T3 syndrome occurred in 29.9% (26/87) of SE cases and patients with low T3 syndrome were more likely to have unfavorable outcomes. Furthermore, we observed similar results in the external cohort, which validated our findings. Conclusions: Serum FT3 levels measured on admission are independently associated with 30-day mortality in SE patients. Additionally, low T3 syndrome may be a promising candidate for predicting SE prognosis.